Analisis Pengaruh Jumlah Wisatawan, Jumlah Kamar Terjual, PDRB per Kapita, dan Inflasi terhadap Realisasi Penerimaan Pajak Hotel Kota Semarang Tahun 2010-2017 - Daniel Victory P; Banatul Hayati (Diponegoro Journal of Economics, 2020)
Fiscal decentralization involves shifting some responsibilities for expenditures and/or revenues to lower levels of government. One important factor in determining revenues is tax. The most potential tax revenues for Semarang City is Hotel Tax. This research aims to analyze the influence of tourist numbers, numbers of sold rooms, GDRP per capita, and inflation towards Hotel Tax revenue realization  in Semarang City. The analytical tool used is multiple linear regression analysis with OLS (Ordinary Least Square). The data used is quartely data from year 2010-2017 obtained  from  the  Badan  Pusat  Statistik  (BPS)  of  Central  Java  Province  and Semarang City, Dinas Kebudayaan dan Pariwisata Semarang City, and Badan Pendapatan Daerah (BAPENDA) Semarang City. The analysis result showed that tourist numbers, numbers of sold rooms, and GDRP per capita has a significant positive effect on hotel tax revenue realization. Whereas   inflation   does   significant   negative   influence   the   hotel   tax   revenue realization